Distance from human settlements favors wild‐type appearance of feral cats (Felis catus) in Mediterranean woodland - Shahar Dubiner; Itai Namir; Ron Chen; Eran Levin (Ecology and Evolution)
Abstract Camouflage is a common trait enabling animals to avoid detection by predators and prey. Patterns such as spots and stripes are convergent across carnivore families, including felids, and are hypothesized to have adaptive value through camouflage. House cats (Felis catus) were domesticated thousands of years ago, but despite artificial selection for a wide variety of coat colors, the wild‐type pattern of tabby cats is very common. We aimed to determine whether this pattern grants an advantage over other morphs in natural environments. We collected cat images taken with camera traps in natural areas near and far from 38 rural settlements in Israel, to compare the habitat use by feral cats of different colors. We tested the effect of proximity to villages and habitat vegetation (normalized difference vegetation index, NDVI) on the probability of space use by the tabby morph compared to the others. NDVI had a positive effect on site use in both morphs, but non‐tabby cats had a 2.1 higher probability of using the near sites than the far sites, independent of NDVI. The wild‐type tabby cats' probability of site use were equally likely to be unaffected by proximity, or have an interaction of proximity with NDVI whereby the far transects are used with increasing probability in sites of denser vegetation. We hypothesize that the camouflage of tabby cats, more than other colors and patterns, confers an advantage in roaming the woodland habitats for which this pattern evolved. This has both theoretical implications as rare empirical evidence of the adaptive value of fur coloration, and practical implications on managing the ecological impact of feral cats worldwide.